Bayi Tabung Menurut Perspektif Islam - Nurmayani Nurmayani; Andin Livia Siagian; Dianra Azriany; Eka Guspi Anti Siregar; Gita Citra Tama; Inda Wati Manik; Naffa Sati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This article explores recent developments in reproductive technology, particularly in vitro fertilization (IVF) and the use of surrogate wombs. It also examines the implications of both methods, particularly in legal, ethical, and religious terms. IVF and surrogate wombs offer solutions for couples facing infertility issues. However, both also carry significant challenges in social and moral dimensions. Using a descriptive approach, this article analyzes various perspectives on the practice, including the Islamic view that generally allows IVF with certain conditions but rejects the use of surrogate wombs. The findings of this study reveal that although reproductive technology offers new hope, it is important to adjust regulations to align with legal, medical, and religious values. Thus, the implementation of this technology can be carried out wisely and humanely.